Application of multivariate methods to identify outstanding broad bean cultivars for the State of Mexico, Mexico - Pérez López Delfina de Jesús; González Huerta Andrés; Franco Mora, Omar; Rubí Arriaga Martín; Ramírez Dávila José Francisco; Castañeda Vildózola Álvaro; Aquino Martínez Jesús Gaudencio (Revista Mexicana de Ciencias Agrícolas, 2018)
The application of multivariate techniques to study the interrelationships between cultivars, environments, variables or their interactions is a valuable tool for identifying outstanding genetic material. This study was conducted in the spring - summer 2011 in San Nicolás Guadalupe (SF), San Mateo Otzacatipan (MO) and Toluca (M), State of Mexico, with the main objective of analyzing the interrelationships between 36 cultivars of broad bean (Vicia faba L.), three locations, and 12 variables. We used the model of additive main effects and multiplicative interaction (AMMI model) and principal component analysis and cluster analysis. The three methods allowed to identify cultivars, environments and salient variables. SF and M were the best seats for the evaluation of genetic material. Cultivars identified as 1, 5, 7 and 36 were superior in the total weight of seed pods per plant, weight of pod per plant, number of seeds per plant, weight of 100 seeds, clean seed weight, seed number clean and number of seeds per pod, they could be used in a breeding program in technology generation, in increasing or seed exchange by farmers who planted or used in commercial planting in the Central State of Mexico, Mexico.